2010
DOI: 10.1080/1059924x.2010.486958
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Language and Literacy Barriers in Safety and Health Training of Agricultural Workers

Abstract: The workforce in all areas of United States agriculture and forestry is becoming increasingly diverse in language, culture, and education. Many agricultural workers are immigrants who have limited English language skills and limited educational attainment. Providing safety and health training to this large, diverse, dispersed, and often transient population of workers is challenging. This review, prepared for the 2010 Agricultural Safety and Health Council of America/National Institute for Occupational Safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 58 publications
1
116
0
8
Order By: Relevance
“…Tarım işletmelerinin büyüklüğü de gerek denetimler gerekse düzenli işgücünün bu alanlarda yaşaması için alt yapı çalışmaları açısından erken ölüm ve hastalıklarla yakından ilişkili bulunmuştur [11]. …”
Section: Devletin Yükümlülükleriunclassified
“…Tarım işletmelerinin büyüklüğü de gerek denetimler gerekse düzenli işgücünün bu alanlarda yaşaması için alt yapı çalışmaları açısından erken ölüm ve hastalıklarla yakından ilişkili bulunmuştur [11]. …”
Section: Devletin Yükümlülükleriunclassified
“…As our findings indicate, a participatory research model (community--based approach) was the most common model for United States researchers to assess and reduce pesticide exposure among migrant farmworkers and their families (30,208,212,225,228). The bulk of these authors argue that community--based participatory research, which engages the community at every stage of the research process, provides a model for mobilizing stakeholders and community members around the issue.…”
Section: Authormentioning
confidence: 99%
“…In addition, the lay health promoter or Promotora de Salud model has been extensively used by advocacy and academic organizations in the United States as a means of reducing migrant farmworkers' exposure to pesticides (30,212). For instance, AmeriCorps Volunteers have been placed in community--based organizations to focus on migrant farmworker pesticide health and safety training.…”
Section: Authormentioning
confidence: 99%
“…The relatively high accident rate in Croatian forestry led Martinic et al (2011) to present a draft national certification for the education of forest workers. Arcury et al (2010) studied the influence of verbal skills on the level of safety in forest workers who do not speak English in the U.S.A. Perhaps the most interesting in this sense is the work by Skinner (2005) resolving the training of forest workers as an essential condition for sustainable forest management. Any research work whose methodology and results would be directly comparable with our study has not unfortunately been found.…”
Section: Education In the 21mentioning
confidence: 99%